Pengembangan Pertanian Kakao Berkelanjutan melalui Inovasi Pestisida Nabati dan Pemberdayaan Masyarakat di Desa Buwun Sejati - Muhammad Zaidaan Ath Thaariq; Sahsandira; Novita Ramdayani; Ahdiyat Rescaya Putra; Thorfinn Muda; Angriani Cahaya Putri; Nery Agustiani; Mufidah; Julia Ariyani; Ni Luh Wirani Putri Wahyuningsih; Misbahuddin (Valid Jurnal Pengabdian, 2026)
Pest control in cocoa cultivation still relies heavily on chemical pesticides, which may negatively affect the environment. This community service activity aimed to improve farmers’ knowledge and skills in producing and utilizing botanical pesticides as an alternative pest control method. The activity was conducted in Buwun Sejati Village, Narmada District, West Lombok Regency through counseling, training, and hands-on practice using cloves, garlic, and galangal. The results showed improved farmers’ knowledge and skills in sustainable pest management. This activity also supports SDGs 2 (Zero Hunger), SDGs 12 (Responsible Consumption and Production), and SDGs 15 (Life on Land) through the implementation of more environmentally friendly and sustainable agricultural practices.